2011
DOI: 10.1002/eco.200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spring drought on carbon sequestration, evapotranspiration and water use efficiency in the songnen meadow steppe in northeast China

Abstract: Global climate change projections suggest an increasing frequency of droughts and extreme rain events in the steppes of the Eurasian region. Using the eddy covariance method, we measured carbon and water balances of a meadow steppe ecosystem in Northeast China during 2 years which had contrasting precipitation patterns in spring We concluded that spring drought detrimentally impacted meadow steppe ecosystem by reducing leaf areas, biomass, GEP, WUE and associated increases in soil evaporation (Es) that might a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 51 publications
8
50
2
Order By: Relevance
“…Crops and grasslands, unable to use water in deeper soil layers because of their relatively short roots, are typically sensitive to droughts (Schwalm et al, 2010a;Wu and Chen, 2013). Droughts might decrease the carbon sequestration capacity of grassland (Dong et al, 2011;Yang and Zhou, 2013), or even change grassland from a carbon sink in "wet" years to a carbon source in "dry" ones (Aires et al, 2008;Jongen et al, 2011). The simulation here shows that the national total of carbon sequestration by grassland in China was negatively affected by drought severity, but not significantly.…”
Section: Drought Sensitivity Of Carbon Sequestration By Different Vegmentioning
confidence: 99%
“…Crops and grasslands, unable to use water in deeper soil layers because of their relatively short roots, are typically sensitive to droughts (Schwalm et al, 2010a;Wu and Chen, 2013). Droughts might decrease the carbon sequestration capacity of grassland (Dong et al, 2011;Yang and Zhou, 2013), or even change grassland from a carbon sink in "wet" years to a carbon source in "dry" ones (Aires et al, 2008;Jongen et al, 2011). The simulation here shows that the national total of carbon sequestration by grassland in China was negatively affected by drought severity, but not significantly.…”
Section: Drought Sensitivity Of Carbon Sequestration By Different Vegmentioning
confidence: 99%
“…Climate models also predict larger climatic variability and more frequent extreme events (e.g. droughts, storms and heat waves) in the future (Dong et al 2011). A more variable PPT regime is likely to occur in the future, being characterized by more extreme rainfall events punctuated by longer intervening dry periods (Thomey et al 2011).…”
Section: List Of Symbols and Abbreviationsmentioning
confidence: 99%
“…The highest carbon sink appeared in central subtropical forests (550±258 g C m -2 yr -1 ), and followed by warm temperate forests (492±37 g C m -2 yr -1 ) and northern subtropical forests (343 g C m -2 yr -1 ). Yu et al, 2013b;Chen et al, 2014;FLUXNET, 2013;Du et al, 2012;Wang et al, 2008;Liu et al, 2011aLiu et al, , 2011bDong et al, 2011aDong et al, , 2011bZhang et al, 2007 Grassland Yu et al, 2013b;Chen et al, 2014 Cool temperate forests showed lower carbon sink compared to warm temperate and temperate forests. Studies of specific ecosystem suggest that mature forests in Northeast, Southeast, and Southwest (Zhang et al, 2006a;Liu et al, 2014a;Tan et al, 2010Tan et al, , 2012Guan et al, 2006;Zhang et al, 2006b;Yan et al, 2012) and subtropical plantations (Liu et al, 2006;Wen et al, 2010) had strong carbon sequestration capacity.…”
Section: Evaluation Of Ecosystem Carbon Sink/source Based On Flux Meamentioning
confidence: 99%